Statistics for business and economics - Anderson, David R. [ (David Ray)] , 1941- (Cengage Learning, 2010)
This volume provides solid methodological development in the area of statistics for business and economics. The development of each technique is presented in an application setting, with statistical results providing insights and solutions to problems